2021
DOI: 10.4103/1673-5374.313017
|View full text |Cite
|
Sign up to set email alerts
|

Epidural electrical stimulation for spinal cord injury

Abstract: A long-standing goal of spinal cord injury research is to develop effective repair strategies, which can restore motor and sensory functions to near-normal levels. Recent advances in clinical management of spinal cord injury have significantly improved the prognosis, survival rate and quality of life in patients with spinal cord injury. In addition, a significant progress in basic science research has unraveled the underlying cellular and molecular events of spinal cord injury. Such efforts enabled the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 92 publications
0
14
0
1
Order By: Relevance
“…We will optimize the fusogen (PEG) and apply electrical stimulation to improve surgical outcomes. 35,36 In addition, mental imagery (MI) therapy will be added to our postoperative rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will optimize the fusogen (PEG) and apply electrical stimulation to improve surgical outcomes. 35,36 In addition, mental imagery (MI) therapy will be added to our postoperative rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this clinical trial, we plan to try to optimize the experimental protocol before expansion of the clinical trial. We will optimize the fusogen (PEG) and apply electrical stimulation to improve surgical outcomes 35,36 . In addition, mental imagery (MI) therapy will be added to our postoperative rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous spinal cord stimulation (TSCS) is a non-invasive neuromodulation technique that can be used to excite sensory neurons in the posterior root of the spinal column. The effects of TSCS are similar to epidural stimulation (ES) that targets the same spinal structures Hofstoetter et al (2018); García et al (2019) and has been shown to be effective in restoring motor function in spinal cord injury (SCI) patients Eisdorfer et al (2020); Rejc et al (2015); Oh et al (2021). However, electrode implantation in ES comes with the risks and expenses of invasive surgery and possible infection after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There is still much to be understood about the mechanisms by which electrical stimulation affects the nervous system and the interaction of the many stimulation parameters, such as stimulation frequency, current amplitude, etc. which affect the outcomes of the interventions Oh et al (2021). We investigate in this study the effects on balance and neurophysiological measures when TSCS is applied to participants performing a functional balance task.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury is a devastating neurological disorder that is associated with life-long neurological condition with motor, sensory, and autonomic deficits (1). Up to 90% of SCI cases are caused by trauma including vehicle crashes, sports injuries, falls or violence (2).The overall global incidence of traumatic spinal cord injury is 10.5 cases per 100,000 person, resulting in an estimated 768,473 new cases annually worldwide , traumatic SCI is one of the major source of morbidity and mortality throughout the world (3). Spinal cord injury (SCI) is a traumatic lifechanging event that has a significant impact on the affected individual as well as the health system.…”
Section: Introductionmentioning
confidence: 99%